Sustainable early design exploration of mid-rise office buildings with different subsystems using comparative life cycle assessment. (1st May 2022) - Zaker Esteghamati, Mohsen; Sharifnia, Houri; Ton, Diep; Asiatico, Patricia; Reichard, Georg; Flint, Madeleine M.
Abstract: Minimizing environmental impacts over a building's life cycle is critical to achieving sustainable communities. Early design is the most critical step to improve construction's sustainability, as the majority of important decisions have not yet been made. However, the implementation of sustainability assessment in early design is data- and effort-intensive, resulting in limited whole building life cycle assessments. Previous studies have mainly focused either on single residential structures, included only a subset of building components, or investigated early design parameters mostly associated with energy efficiency. Whereas, comparison of alternative building subsystems at early design received less attention. This study aims to provide and utilize benchmark data for the life-cycle impacts of mid-rise office buildings, focusing on the impact of building subsystem selection at early design exploration. Environmental impacts were compared across six professionally-designed archetypes comprising compatible combinations of foundation, floor, and structural assemblies for a site in Charleston, South Carolina. Detailed operational energy modeling was performed using the EnergyPlus framework, where a range of code-compliant envelope systems are studied and paired with other assemblies. Lastly, sensitivity assessment and statistical analysis are performed to quantify uncertainty associated with the use of such data for early design guidance. The results suggest that decisions associated with the use phase (such as envelope selection) dominates life cycle impacts and should be prioritized. Additionally, no single subsystem governs all embodied impacts across different buildings. Lastly, it is critical to consider a large number of alternatives at the early design stage, as excluding a combination of subsystems might close pathways to reaching a more environmentally suitable alternative during design iterations/optimization. Highlights: Evaluate the environmental performance variability of six professionally-designed commercial buildings comprising different combinations of foundation, structural and envelope subsystems. Assess the sensitivity of embodied and operational environmental impacts to identify the most influential early design decisions. Introduce environmental performance inventory by aggregating literature and simulation and apply statistical inference to deduce subsystem selection guidance. A sustainable early design should evaluate a large number of subsystem combinations at the divergence phase since optimization cannot always offset the exclusion of a more environmentally suitable alternative at later design stages.